2020
DOI: 10.1016/j.jaip.2020.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Early experiences of SARS-CoV-2 infection in severe asthmatics receiving biologic therapy

Abstract: We present an early experience with patients with severe asthma treated with different biologics and affected by severe acute respiratory syndrome coronavirus 2 infection.AZT, Azithromycin; kU: kilounit; PRN, as needed. *5 mg prednisone/24 h.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 7 publications
5
12
0
Order By: Relevance
“…Acute communicable diseases represent the most common clinical conditions in children; in fact, up to 11 respiratory tract infections per year in infancy, 8 episodes per year at pre-school age, and 4 episodes per year at school age could be considered as normal [ 64 ]. Our results are also reinforced by several studies that have shown a reduction in the exacerbation of chronic conditions during lockdown period [ 65 ], such as asthma [ 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ] and cystic fibrosis [ 74 ]. The reduction in total ER admissions can be also explained by parents’ fear of leaving their home and of being infected in the hospital [ 50 , 75 , 76 ], and the explicit order to avoid going to the ER unless in cases of extreme medical necessity [ 37 , 38 ].…”
Section: Discussionsupporting
confidence: 82%
“…Acute communicable diseases represent the most common clinical conditions in children; in fact, up to 11 respiratory tract infections per year in infancy, 8 episodes per year at pre-school age, and 4 episodes per year at school age could be considered as normal [ 64 ]. Our results are also reinforced by several studies that have shown a reduction in the exacerbation of chronic conditions during lockdown period [ 65 ], such as asthma [ 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ] and cystic fibrosis [ 74 ]. The reduction in total ER admissions can be also explained by parents’ fear of leaving their home and of being infected in the hospital [ 50 , 75 , 76 ], and the explicit order to avoid going to the ER unless in cases of extreme medical necessity [ 37 , 38 ].…”
Section: Discussionsupporting
confidence: 82%
“…We found that monoclonal antibodies for asthma were not associated with increased risk of mild or severe COVID-19 infection. This agrees with other emerging findings of low incidence of COVID-19 in the severe asthma population and biologics not affecting clinical outcome (7). Poor asthma control increases the risk of severe viral exacerbations, so disease stability from biologics may be protective in itself (8).…”
supporting
confidence: 90%
“… 3 , 5 However, other studies report that asthma may increase COVID-19 susceptibility and disease severity. 7 Other European reports on patients with asthma with COVID-19 show similar trends as those found in Spain 8 and in other series published in the United States. 9 With the data from this cohort, we hypothesize that biological treatment for severe uncontrolled asthma does not represent a risk factor for COVID-19, in terms of infection or severity, and there are no significant differences among patients treated with different biological drugs.…”
supporting
confidence: 71%